2012
DOI: 10.1080/15374416.2012.632343
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial Comparison of Emotion Regulation and Relational Psychotherapies for PTSD with Girls Involved in Delinquency

Abstract: Posttraumatic stress disorder (PTSD) is prevalent in youth involved in delinquency, but it is often not effectively treated. A randomized clinical trial was conducted comparing the outcomes of an emotion regulation therapy (Trauma Affect Regulation: Guide for Education and Therapy, or TARGET) with a relational supportive therapy (Enhanced Treatment as Usual, or ETAU) with 59 delinquent girls (age 13-17 years) who met criteria for full or partial PTSD. Mixed model regression analyses demonstrated generally larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(96 citation statements)
references
References 63 publications
3
92
1
Order By: Relevance
“…Since the publication of the meta-analyses by Silverman et al (2008) and Gillies et al (2012), several RCTs on the efficacy of interventions for pediatric PTSD have been published (Carrion, Kletter, Weems, Berry, & Rettger, 2013;Danielson et al, 2012;Diehle, Opmeer, Boer, Mannarino, & Lindauer, 2015;Foa, McLean, Capaldi, & Rosenfield, 2013;Ford, Steinberg, Hawke, Levine, & Zhang, 2012;Jensen et al, 2014;McMullen, O'Callaghan, Shannon, Black, & Eakin, 2013;O'Callaghan, McMullen, Shannon, & Rafferty, 2015;O'Callaghan et al, 2014;O'Callaghan, McMullen, Shannon, Rafferty, & Black, 2013;Schottelkorb, Doumas, & Garcia, 2012;Tol et al, 2014). The goal of the present study was to provide an updated quantitative, meta-analytic review of the efficacy of interventions for children and adolescents suffering from PTSD.…”
mentioning
confidence: 96%
“…Since the publication of the meta-analyses by Silverman et al (2008) and Gillies et al (2012), several RCTs on the efficacy of interventions for pediatric PTSD have been published (Carrion, Kletter, Weems, Berry, & Rettger, 2013;Danielson et al, 2012;Diehle, Opmeer, Boer, Mannarino, & Lindauer, 2015;Foa, McLean, Capaldi, & Rosenfield, 2013;Ford, Steinberg, Hawke, Levine, & Zhang, 2012;Jensen et al, 2014;McMullen, O'Callaghan, Shannon, Black, & Eakin, 2013;O'Callaghan, McMullen, Shannon, & Rafferty, 2015;O'Callaghan et al, 2014;O'Callaghan, McMullen, Shannon, Rafferty, & Black, 2013;Schottelkorb, Doumas, & Garcia, 2012;Tol et al, 2014). The goal of the present study was to provide an updated quantitative, meta-analytic review of the efficacy of interventions for children and adolescents suffering from PTSD.…”
mentioning
confidence: 96%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Psychotherapeutic interventions were marked by substantial heterogeneity in components, dose, frequency, involvement of family members, and mode and method of delivery. The wide variety of approaches presented challenges in how to best combine and categorize the psychotherapeutic interventions in particular.…”
Section: Results Of Literature Searchesmentioning
confidence: 99%
“…22,23,[25][26][27][28][29]33,[35][36][37][38] Six studies reported no improvement in one or all outcomes evaluated. 25,26,29,33,35,38 One 22 of 5 interventions reported in 6 studies 22,26,29,35,37,38 evaluating anxiety symptoms showed improvements (TF-CBT); 4 interventions reported in 5 studies 22,23,27,29,36 of 10 interventions reported in 12 studies 22,23,[25][26][27][28][29]33,35,[36][37][38] showed improvement in depression; 2 studies found no improvement in internalizing behaviors. 26,38 Two studies evaluated physical symptoms or general health outcomes; neither found evidence of benefit.…”
Section: Treatment Based On Exposure and Already-occurring Symptomsmentioning
confidence: 94%
See 1 more Smart Citation
“…The use of MI has shown positive, offending-reduction effects on justice-involved individuals (Hohman, Doran, & Koutsenok, 2009). Although there have not been specific studies examining the use of MI with identified gang or crew members, the use of MI with serious offenders has been shown to be successful, in terms of both a better client-service provider relationship and improved criminal justice compliance with males (Schwalbe & Maschi, 2011) and with females (Ford, Steinberg, Hawke, Levine, & Zhang, 2012). Further, a systematic review of MI studies shows that social service clients were more engaged and had higher retention and lower offending when MI was used (McMurran, 2009).…”
Section: Interventions With Gangs and Crewsmentioning
confidence: 92%